Determinants of Islamic banking value: Financial performance as a mediation - Thohari, Imam; Sasongko, Noer; Bawono, Andy Dwi Bayu (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: The objective of this research is to test and empirically prove what factors have the most influence on the performance of Islamic banking so that they can take appropriate action policies to increase the competitiveness and value of the company in the market.Design/Methodology/Approach: Quantitative methodology with secondary data from 102 data samples is used. The data is panel data and processed with views. Hypothesis testing is used to determine the effect of intellectual capital, corporate governance, maqashid sharia index (MSI), and enterprise risk management (ERM) on financial performance. Mediation tests to determine financial performance mediate intellectual capital, corporate governance, MSI, and corporate risk management on Islamic banking value.Research findings: Financial performance has not been able to mediate the relationship between intellectual capital, corporate governance, MSI, and ERM in relation to the value of Islamic banking.Theoretical contribution/Originality: This study extends previous research on factors that can increase the value of Islamic banking in Indonesia by using ERM, which has not been widely studied in Indonesia.Practitioner/Policy implication: This study provides important insights into which areas need to be improved or further evaluated to enhance future corporate performance and the value of Islamic banking.Research limitations/Implications: There is a possibility that important variables that can affect the results, such as external economic or political factors, are not controlled in this study. It is hoped that further research will use a wider sample and a longer observation period so that research findings can generalize the results of research on financial performance and company value.